Employee Perceptions Of The Influence Of Job Satisfaction And Self-Efficacy On Retention Decisions At PT. Sumo Internusa - Wiwin Surtinah (Pasundan Social Science Development, 2025)
This study aims to examine employee perceptions of the influence of job satisfaction and self-efficacy on employee retention decisions at PT Sumo Internusa. The method used was a qualitative approach with an in-depth interview approach with 15 employees selected based on certain criteria, to obtain in-depth information regarding the factors influencing their retention decisions. The results showed that job satisfaction has a significant influence on employee decisions to remain with the company. Factors such as a conducive work environment, adequate compensation, and good relationships with superiors and coworkers are important elements in shaping job satisfaction levels. Meanwhile, self-efficacy, which reflects employees' confidence in their abilities to perform their duties, also plays a role in retention decisions. Employees with high levels of self-efficacy tend to be more satisfied with their jobs and more committed to remaining with the company. This study reveals that companies need to consider both factors in their employee retention strategies, in order to retain quality human resources and reduce employee turnover rates.